1982
DOI: 10.2337/diab.31.9.834
|View full text |Cite
|
Sign up to set email alerts
|

Glucose but not Arginine Prevents the Inhibitory Effect of Vincristine on Glucose-induced Insulin Release

Abstract: SUMMARYWe have previously shown that in the intact rat: (1) the inhibition of glucose-induced insulin release caused by vincristine occurred in the presence or absence of morphologic disruption of the beta-cell microtubules; and (2) vincristine, however, failed to inhibit arginine-induced insulin release, even in the presence of a marked disruption of the beta-cell microtubules. The present study further evaluated the mechanism of inhibition of vincristine on glucose-induced insulin release in the intact rat. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
1987
1987

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…For example, colchicine has been shown to affect concanavalin A receptors on white blood cells (Madyastha et al 1977). Dissociation of the effects of vincristine on the beta cell microtubular struc¬ tures and on the stimulated insulin release ob¬ served in our previous studies have shown that the effect of these agents on insulin release is mediated by mechanisms other than microtubular dis¬ ruption (Shah et al 1979(Shah et al , 1981(Shah et al , 1982a(Shah et al , 1982b). …”
Section: Discussionmentioning
confidence: 91%
“…For example, colchicine has been shown to affect concanavalin A receptors on white blood cells (Madyastha et al 1977). Dissociation of the effects of vincristine on the beta cell microtubular struc¬ tures and on the stimulated insulin release ob¬ served in our previous studies have shown that the effect of these agents on insulin release is mediated by mechanisms other than microtubular dis¬ ruption (Shah et al 1979(Shah et al , 1981(Shah et al , 1982a(Shah et al , 1982b). …”
Section: Discussionmentioning
confidence: 91%